478 A qualitative exploration of the implementation of the Prescribing course Designated Prescribing Practitioner role in community pharmacy. (13th April 2023) - Jebara, T; McIntosh, T; Stewart, F; Osprey, A; Bruce, R; Cunningham, S
Abstract: Introduction: To alleviate NHS workload pressures Scottish Government wish to train more pharmacist independent prescribers (IPs) for community pharmacy (1). A critical aspect for IP training is the role of Designated Prescribing Practitioner (DPP) for the period of learning in practice. A paucity of work has focussed on implementation of the DPP role with a recent cross-sectional survey (2) indicating that further qualitative exploration is warranted. Aim: To explore the implementation of the DPP role in Scottish Community Pharmacy (CP). Methods: Following a survey (2) participants opted in to qualitative semi-structured online mini-focus groups. This included key stakeholders likely be involved in the implementation of the DPP role (e.g Directors of Pharmacy, Prescribing Leads, Education and Training leads, IP qualified CPs). The topic guide was informed by the survey key findings, Royal Pharmaceutical Society DPP Framework and the Consolidated Framework for Implementation Research and piloted with academic and practice-based stakeholders. All focus groups were conducted using Zoom, recorded, transcribed, and independently analysed thematically, by two researchers, using the Framework Approach. Data generation continued until data saturation. Results: Data were generated from six mini-focus groups with 12 key stakeholders across Scottish Health Boards. Key themes derived related to: views on the DPP role, characteristics of potential DPPs, facilitators and barriers to implementation. Participants supported DPP implementation and noted benefits of pharmacists training pharmacists. They noted that potential DPPs need to be confident and competent and be active prescribers. Facilitators for implementation included: new contracted services (e.g. NHS Pharmacy First Plus), growing need for more IPs, and the impact of COVID-19. Barriers included: limited time, capacity, resources, and support to take on the DPP role. Pharmacists were also considered risk averse which could influence role uptake. Conclusion: This theory-based work involved a range of key stakeholders and highlights that there is a need to further consider interventions to overcome barriers related to capacity and resource related issues. A limitation relates to the dyadic nature of some focus groups that may have affected data collection. Future research should focus on further theory-based work evaluating structures, processes, and outcomes of DPP role implementation. References: 1. Scottish Government. Community pharmacy – national career pathway and introduction of a common clinical conditions independent prescribing service (NHS pharmacy first plus). [online]. Edinburgh: Scottish Government. 2020. Available from: https://www.sehd.scot.nhs.uk/pca/PCA2020(P)16.pdf Accessed 14 Oct 2022. 2. Jebara, T., McIntosh, T., Stewart, F. et al. Designated prescribing practitioners: a theory-based cross-sectional study of stakeholders' views on implementation of a novel pharmacy regulator mandated preceptorship model. Int J Clin Pharm. 2022; 44:1195–1204. Available from https://doi.org/10.1007/s11096-022-01467-8 Accessed 14 Oct 2022.